Beyond Boundaries: Rethinking Human-Animal Bonds in Richard Powers’s The Overstory (American Journal of Arts and Human Science, 2025)
This article examines human-animal relationships in Richard Powers’s The Overstory (2018), aiming to contribute to the ongoing discussion about animal portrayals in literature by suggesting that the book challenges the divisions between humans and animals. While the novel has been widely studied for its ecocentric view and its fresh reading of the human-plant link, it argue that Powers’s story also makes room for animals as aware, purposeful, and morally important beings. Drawing from critical animal studies, posthumanism, and ecocriticism, this research explores how the novel questions human-centered standards and places animals within a wider web of ecological links. Through characters like Patricia Westerford, Douglas Pavlicek, and Olivia Vandergriff, the novel shows a kind of multispecies ethic where animals are not just background figures but also active parts of the story and important moral players. Powers’s animals—both real and imagined—are not just passive victims of ecological problems; they are co-inhabitants whose lives are closely tied to human actions. In doing this, The Overstory shows a change in literature toward the more-than-human view that is a focus of environmental humanities. It suggests that literature can be a key tool for ethics, able to shift how we see other species during an age of ecological problems and extinctions. Powers’s work presents a chance in modern fiction to imagine connections that move past human-focused ideas.